Pertinence of universal design and accessibility in mosque for people with disabilities / Farah Nuratiqah Rusli and Md Azree Othuman Mydin - Rusli, Farah Nuratiqah; Othuman Mydin, Md Azree (2018)
Malaysia is a country which is known for the heavy Islamic moral values presence in its culture and traditions. Mosques in Malaysia are well known for their beauty and captivating architecture. There are 5,300 mosque that have been built in Malaysia until November 2017 and it is increasing as the years go by but the accessibility of amenities for the Persons with Disabilities (PwDs) is still a major problem. The mosque is not just for those without disability; therefore it is important to provide them an equal opportunity to perform congregational prayers together with other devoted Muslims and help them perform their responsibility and their social roles. All the way through history, community attitudes and physical obstructions in the built environment have barred PwDs from fully participating in the society. These days, along with the emergence in the PwDs population, the mission for impartiality and equal rights has become fully-fledged. Currently, major changes in design requirements, both market-driven and legally mandated, are creating a new life system for People with Disabilities (PwDs) and a new path for designers. Hence this study focuses on the appraisal of accessibility of amenities in 10 mosques in Penang using requirements from the current Malaysian Standards for accessibility; MS1184:2014 Code of Practice on Access for Disabled Persons to Public Buildings. The methodology of this research considers conducting access audit of case studies, observations on site and semi-structured interviews. The expected findings are to identify whether the facilities provided match the needs of the people with disabilities. This is further supported by using the Malaysian standard (MS 1184:2014) Universal Design that fits and matches the facilities provided for various types of People with Disabilities PwDs. The access audit was done so as to assess the accessibility of facilities provision. Besides that, a semi structured interview was also conducted. The results reveal that most of the facility provisions for the disabled provided in the mosque comply with the standard MS1184:2002, but the important provision such as ramps, toilet facilities and hand rails still do not comply with this standard.